Sick of your job? Negative health effects from non-optimal employment - Jan Kleibrink (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In an empirical study based on data from the German Socio-Economic Panel, the effect of job quality on individual health is analyzed. Extending previous studies methodologically to estimate unbiased effects of job satisfaction on individual health, it can be shown that low job satisfaction affects individual health negatively. In a second step, the underlying forces of this broad effect are disentangled. The analysis shows that the effects of job satisfaction on health run over the channels of job security and working hours above the individual limit. Job quality not only has a strong impact on mental health but physical health is affected as well. At the same time, health-damaging behavior including smoking and being overweight is not affected.
Keywords: I14; J24; J28; 330; Individual Health; Job Satisfaction